Crime and criminal investigation in Nigeria: a study od police criminal investigation in Enugu State - Chinwokwu, Eke Chijioke (African journal of law and criminology, 2012)
This study inquired into the activities of the police in crime and criminal investigation with particular focus on the Police Criminal Investigation in Enugu State Police Command. The specific objectives of the study include: (1) an examination of the factors responsible for the high rate of ‘undetected’ and ‘pending investigation’ of criminal cases in Enugu State (2) an investigation of the training skills and strategies adopted by the police officers in criminal investigation (3) an assessment of the effectiveness of such techniques (4) an identification of the challenges confronting the police in criminal investigations. A total of 330 respondents were selected for the study. Data were colltected through the use of questionnaires, oral interviews, as well as from documents and crime statistics. Data generated through questionnaire were analyzed using descriptive techniques such as frequency count and percentage while the data obtained through interviews and documentary sources were content analyzed. The findings revealed that factors such as lack of training, skills, facilities, corruption, disobedience to due process and ethical standard among others account for the high rate of ‘undetected’ and ‘pending cases’ of criminal investigations in Nigeria as well as Enugu State. It also shows that the investigative strategies and techniques adopted by the police are not effective enough in addressing the challenges facing the police criminal investigation department.